2017
DOI: 10.1080/10790268.2017.1368203
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of cardiometabolic health are associated with body composition characteristics but not physical activity in persons with spinal cord injury

Abstract: Objective To examine (i) the associations between physical activity dimensions, cardiorespiratory fitness and body composition and, (ii) the associations between physical activity dimensions, cardiorespiratory fitness, body composition and biomarkers of cardiometabolic health in persons with spinal cord injury (SCI). Methods A cross-sectional prospective cohort study with 7-day follow-up was conducted. Body composition, cardiorespiratory fitness and biomarkers of cardiometabolic health were measured in thirty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…Some of the lower VO 2peak values in the PAthl with SCI (see Figure 1) can also be explained by their lesion level. It has been reported indeed that the VO 2peak is inversely related to the lesion level in individuals with paraplegia (Bernard et al, 2000;Janssen et al, 2002;Nightingale et al, 2019), i.e., the higher the lesion level the lower the VO 2peak . In the current study, the lesion level of the 19 PAthl with SCI ranged from T4 to L1.…”
Section: Peak Cardiorespiratory Responsesmentioning
confidence: 96%
“…Some of the lower VO 2peak values in the PAthl with SCI (see Figure 1) can also be explained by their lesion level. It has been reported indeed that the VO 2peak is inversely related to the lesion level in individuals with paraplegia (Bernard et al, 2000;Janssen et al, 2002;Nightingale et al, 2019), i.e., the higher the lesion level the lower the VO 2peak . In the current study, the lesion level of the 19 PAthl with SCI ranged from T4 to L1.…”
Section: Peak Cardiorespiratory Responsesmentioning
confidence: 96%
“…Decreased fat mass is likely to improve parameters of cardio-metabolic health after SCI[ 11 ]. A recent report demonstrated that improvement in cardio-metabolic health is tightly associated with positive body composition characteristics compared to parameters of physical activity[ 19 ]. There is still limited evidence to support the positive effects of exoskeleton ambulation on parameters of body composition.…”
Section: Benefits and Limitations From Health Prospectivementioning
confidence: 99%
“…Waist circumference will be measured in the supine position following a normal expiration to the nearest 1 cm midway between the lowest lateral border of the ribs and the uppermost lateral iliac crest. Waist circumference is considered the most practical surrogate for VAT in individuals with SCI and is tightly associated with cardiometabolic disease biomarkers 24…”
Section: Methods and Analysismentioning
confidence: 99%
“…However, a recent 16-week randomised controlled trial, whereby participants performed ≥40 min/week moderate-to-vigorous upper body exercise and resistance training, showed no improvement in CVD risk factors (ie, arterial stiffness, endothelial function, body composition parameters and metabolic profile) 23. Moreover, cross-sectional data suggest that objectively measured physical activity is not associated with biomarkers of cardiometabolic disease risk in individuals with paraplegia 24. Given these findings, the small sample sizes and considerable variability in the existing exercise training literature in individuals with SCI with regards to (1) the exercise intervention tested (ie, exercise modality, frequency, duration, intensity), (2) participant demographics, (3) research design and (4) outcome measures collected, it is currently challenging to provide evidence-based exercise prescriptions.…”
Section: Introductionmentioning
confidence: 98%